2013
DOI: 10.1353/pbm.2013.0004
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference Clinical Trials: Why and When They Will Sometimes Be Preferred

Abstract: In a preference clinical trial (PCT), two or more health-care interventions are compared among several groups of patients, at least some of whom have purposefully chosen the intervention to be administered to them. This stands in contrast to the randomized, controlled clinical trial (RCT), where patients are randomly assigned to receive one of the available test interventions. This article argues that when comparing two interventions, A and B, when blinding (or masking) the interventions is difficult or imposs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…Therefore, a partially randomised patient preference trial (PRPP) design was used, in line with the study of Cooper et al 29 and Henshaw et al 30 . As discussed in our earlier study 24 , this kind of experimental design is preferred when the blinding of the interventions is difficult or impossible and some of the potential participants prefer one or other of the interventions 28,31 . King et al 32 suggested in their systematic literature review, when participants declare strong preferences against one particular intervention arm in randomised controlled trials, the PRPP design could be used to prevent any bias by reducing or removing a preference/motivation effect when evaluating motivation-based studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a partially randomised patient preference trial (PRPP) design was used, in line with the study of Cooper et al 29 and Henshaw et al 30 . As discussed in our earlier study 24 , this kind of experimental design is preferred when the blinding of the interventions is difficult or impossible and some of the potential participants prefer one or other of the interventions 28,31 . King et al 32 suggested in their systematic literature review, when participants declare strong preferences against one particular intervention arm in randomised controlled trials, the PRPP design could be used to prevent any bias by reducing or removing a preference/motivation effect when evaluating motivation-based studies.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a partially randomised patient preference trial (PRPP) design was used, in line with the study of Cooper et al 29 and Henshaw et al 30 . As discussed in our earlier study 24 , this kind of experimental design is preferred when the blinding of the interventions is difficult or impossible and some of the potential participants prefer one or other of the interventions 28,31 . King et al…”
mentioning
confidence: 99%
“…This allows that extra-genetic information, e.g., clinical/environmental, will inform personalization of care. Indeed, we suggest that there may be other sources of information, not usually categorized as clinical, environmental, or genetic, e.g., patient preferences [24], that should be taken into account in tailoring treatment. Accordingly, we follow Gamma [25], by adopting a broad definition of personalized medicine as the attempt to improve health by any means that makes treatments more individual-specific, more targeted, and more effective, while at the same time minimizing adverse side-effects.…”
Section: Personalized Medicinementioning
confidence: 99%
“…Their adaptation of the IOM definition of CER is that it "seeks to inform clinical decisions between alternate treatment strategies using data that reflects real patient populations and real-world clinical scenarios for the purpose of improving patient outcomes" and "to combine treatment efficacy data with quality of life, outcomes, and other forms of effectiveness data to guide selection of optimal patient management strategies" (989). The first part of this statement clearly underscores the potential utility of observational studies, in that they are, by definition, based in the real world where patients have preferences, help make treatment decisions, are variably compliant, have other conditions and may be taking other drugs to treat them (Kowalski and Mrdjenovich 2013a). The second part admits to the role that RCTs have in establishing efficacy, but implicitly notes that while efficacy may be necessary for a treatment to be considered a viable option, it is not sufficient to cement a decision.…”
Section: Observational Studiesmentioning
confidence: 99%
“…In addition, the R part of the RCT is not always necessary or possible. Marko and Weil (2010) describe four situations where randomization cannot or need not be applied: randomization may not be necessary (when the effect under study is dramatic and possible confounding effects negligible); it may be impossible (clinicians or patients refuse to participate); it may be unethical (equipoise may not exist); or it may be self-defeating (when the effectiveness of the intervention depends on the subjects' active participation in or knowledge of the treatment (Kowalski 2013;Kowalski and Mrdjenovich 2013a). 5 Observational studies can often prove useful in these cases, and, when appropriate, the methods described in the preceding section can be employed.…”
Section: Pragmatic Trialsmentioning
confidence: 99%